Intenção empreendedora universitária: um estudo de caso sobre fatores determinantes da intenção empreendedora dos universitários - Lopes, Matheus de Carvalho (2024)
This research explores Entrepreneurial Intention (EI) among undergraduate students majoring in Business Administration at UFAM. The overall objective was to analyze phenomena associated with EI, adopting a quantitative and descriptive research approach. The methodology employed a questionnaire based on the Theory of Planned Behavior (TPB), including demographic questions. The sample consisted of 107 students, with a significant predominance in the age range of 18 to 24 years (84.1%). Factor analyses highlighted a strong positive influence of Subjective Norms, indicating robust social support for entrepreneurship. Regarding Perceived Behavioral Control, capabilities showed discrepancies, while knowledge received agreements, indicating uncertainties in specific skills.